Big data computing and communications : second International Conference, BigCom 2016, Shenyang, China, July 29-31, 2016, Proceedings /: second International Conference, BigCom 2016, Shenyang, China, July 29-31, 2016, Proceedings. (2016) - Unknown
No abstract available